IMPLEMENTATION OF KAMPUNG TURIS PARKING POLICY BY KARANG TARUNA WONOHARJO VILLAGE PANGANDARAN DISTRICT PANGANDARAN REGENCY - Mira Meriyani; Irfan Nursetiawan; Asep Nurdin Rosihan Anwar (Faculty of Social and Political Science Universitas Galuh, 2023)
This research is motivated by the not yet optimal implementation of the policy for the management of the Kampung Turis parking lot by the Youth Organizations in Wonoharjo Village, Pangandaran District, Pangandaran Regency withInadequate parking facilities and infrastructure where there is no adequate parking space, there is no marking line for parking vehicles or Parking Space Units (SRP), Lack of discipline of parking officers in the collection of parking taxes in the Tourist Village, Wonoharjo Village, Pangandaran District, Pangandaran Regency, and has not there is guidance for parking officers from the Pangandaran Regency Transportation Service. Based on the research results that the implementation of the policy for managing the parking lot of the Kampung Turis by Karang Taruna, Wonoharjo Village, Pangandaran District, Pangandaran Regency, has not been optimal, with many problems in its implementation such as inadequate facilities and infrastructure in policy implementation, lack of understanding of officers on the contents of the policy, and no clear delegation of authority. from the government to officers in implementing policies, policy information has not been conveyed clearly by officers to the public regarding policy implementation, there is no integrated and consistent communication between officers and the community, organizations and related agencies, there is no adequate budget support in implementing the policy and there is no regulatory support in implementing the policy for the management of the Kampung Turis parking lot.